Reliability and Validity of the Malay Version of Edinburgh Postpartum Depression Scale (EPDS) When Administered to Postpartum Mothers at Two Points in Time - MA, Nursazila Asikin; S, Siti Norhani; AR, Nur Arzuar; O, Eshaifol Azam (IIUM Medical Journal Malaysia, 2019)
Introduction: Edinburgh Postpartum Depression Scale (EPDS) is a tool used to assess the risk of postpartum depression (PPD). In this study we determined the reliability and validity of the Malay version of EPDS when administered at two different time points in the postpartum period. Materials and Methods: This cross-sectional study design was carried out between May and September 2017 at three government primary healthcare clinics located in Batang Padang district, a suburban area of Perak state in Peninsular Malaysia. We recruited a total of 89 women; 41 women were in the early postpartum period (1-30 days) and 48 women were in the late postpartum period (31-120 days). Cronbach's alpha coefficient, inter-item correlation, and corrected item-total correlation were used to assess the internal consistency. The concurrent validity was assessed using Spearman’s correlation. The data were analyzed using SPSS version 20 and R 3.4.2. Results: The Cronbach’s alpha for the first and second group was 0.78 and 0.62, respectively, which indicated satisfactory reliability. At both time periods, removing Item 2 from the scale resulted in a significant increase in Cronbach’s alpha (to 0.847 and 0.709, respectively). As expected, the EPDS scores correlated moderately with the BDI-II scores (1−30 days: Spearman's rho = 0.65, p < 0.01; 31−120 days: Spearman's rho = 0.73, p < 0.01). Conclusion: The Malay version of the EPDS is a reliable screening instrument for detecting postpartum depression. It showed reasonability and feasibility and can be used in postpartum clinical settings or for assessing intervention effects in research studies. Furthermore, as our results indicated, removing Item 2 from the Malay version would increase the internal consistency of the EPDS.